Numerical Hull Resistance Calculation of a Catamaran using OpenFOAM - Espol (2019)
An accurate estimation of ship resistance is essential for the selection of the engines to achieve the required speed of navigation. In traditional ships, resistance is decomposed in frictional and wave components. In addition, for catamarans the interaction between its hulls has to be considered. In the present study, numerical resistance predictions using OpenFOAM were performed considering the Cormorant Evolution Catamaran, which provides travel services in the Galapagos Islands. These predictions were compared with experimental data published by Chávez and Lucín [1] and with systematic series [2]. Simulations were made at model scale of 2 [m] in two load conditions, considering demi and twin hull (S=0.56 [m]) configurations, following the experimental procedure done in [1]. A mesh convergence study was performed with 3 different meshes for V=1.05 [m/s] at Light Condition (T=0.086 [m]). The converged mesh, with 1 million of cells approximately